Hepatic encephalopathy treatment after transjugular intrahepatic portosystemic shunt: a new perspective on the gut microbiota - Xu, Xiaotong; Zhu, Tong; Jing, Changyou; Jiang, Minjie; Fu, Yunlai; Xie, Fang; Meng, Qinghua; Li, Jianjun (Frontiers in Medicine, 2025)
Transjugular intrahepatic portosystemic shunt (TIPS) placement alleviates portal hypertension symptoms. Hepatic encephalopathy (HE) is a common complication of TIPS, impacting patient quality of life and the healthcare burden. Post-TIPS HE is associated with portosystemic shunting, elevated blood ammonia levels, and inflammation. Increasing attention has been given to the liver and intestinal circulation in recent years. An imbalance in intestinal microecology plays a role in the occurrence of HE and may be a new target for treatment. This review discusses the causes, diagnosis, and treatment strategies for post-TIPS HE and focuses on exploring treatment strategies and their relationships with the gut microbiota, suggesting an innovative approach to address this complication.